2015
DOI: 10.1186/s40064-015-1358-z
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian and Singaporean students’ affective characteristics and mathematics performance: evidence from PISA 2012

Abstract: This paper attempts to identify the extent to which the affective characteristics of Malaysian and Singaporean students’ attainment compared to the OECD average in Programme for International Student Assessment (PISA) 2012, and examine the influence of students’ affective characteristics, gender, and their socioeconomic status on mathematics performance at both student and school levels. Sample consisted of 5197 and 5546 15-year-old Malaysian and Singaporean students. Data were analysed using hierarchical line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 43 publications
(43 reference statements)
7
29
2
5
Order By: Relevance
“…In relation to the relatively low mathematics test scores, it seems possible that these results were due to students' frustration and helplessness while answering the test questions could have been challenging to them. This result is similar to that of PISA 2012 in which Malaysian students had significantly higher levels of instrumental motivation and mathematical interest compared to OECD average but had a higher level of mathematics anxiety than OECD average too (OECD, 2014;Thien & Ong, 2015). One possible reason for this is that students could be feeling anxious about mathematics while being well aware of its utility value in the Malaysian education context.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In relation to the relatively low mathematics test scores, it seems possible that these results were due to students' frustration and helplessness while answering the test questions could have been challenging to them. This result is similar to that of PISA 2012 in which Malaysian students had significantly higher levels of instrumental motivation and mathematical interest compared to OECD average but had a higher level of mathematics anxiety than OECD average too (OECD, 2014;Thien & Ong, 2015). One possible reason for this is that students could be feeling anxious about mathematics while being well aware of its utility value in the Malaysian education context.…”
Section: Discussionsupporting
confidence: 80%
“…classroom practices). In a related vein, Thien and Ong (2015) highlighted that in PISA 2012, unlike affective variables like mathematics self-efficacy and anxiety, mathematical interest did not significantly relate to Malaysian students' mathematics performance. In view of these inconclusive findings, this study intended to investigate the relationship between interest and mathematics performance among Malaysian students in a technology-enhanced learning environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students may easily get bored and dislike mathematics if they could not solve mathematical problems. However, the study made by Thien and Ong [8] found that Malaysian students loved studying Mathematics and they believed that mathematics is necessary for their future careers despite of their mathematics competency.…”
Section: Introductionmentioning
confidence: 99%